PTSD Symptoms and Pain in Canadian Military Veterans: The Mediating Roles of Anxiety, Depression, and Alcohol Use. Issue 2 (17th March 2014) - Irwin, Kara C.; Konnert, Candace; Wong, May; O'Neill, Thomas A.
<x xml:space="preserve">Abstract</x> Symptoms of posttraumatic stress disorder (PTSD) and pain are often comorbid among veterans. The purpose of this study was to investigate to what extent symptoms of anxiety, depression, and alcohol use mediated the relationship between PTSD symptoms and pain among 113 treated male Canadian veterans. Measures of PTSD, pain, anxiety symptoms, depression symptoms, and alcohol use were collected as part of the initial assessment. The bootstrapped resampling analyses were consistent with the hypothesis of mediation for anxiety and depression, but not alcohol use. The confidence intervals did not include zero and the indirect effect of PTSD on pain through anxiety was .04, CI [.03, .07]. The indirect effect of PTSD on pain through depression was .04, CI [.02, .07]. These findings suggest that PTSD and pain symptoms among veterans may be related through the underlying symptoms of anxiety and depression, thus emphasizing the importance of targeting anxiety and depression symptoms when treating comorbid PTSD and pain patients.